Phylogenetisch-systematische Revision des Genus Temnorhynchus Hope, 1837 (Coleoptera: Scarabaeoidea: Melolonthidae: Dynastinae: Pentodontini). 2. Teil: Bestimmungstabelle, Katalog, Bibliographie, Gazetteer und Material-Listen. - Krell, Frank-Thorsten (Contributions to Entomology = Beiträge zur Entomologie, 1994)
Subsequent to a phylogenetic analysis of the genus Temnorhynchus Hope a key to species and subspecies is given. The lectotype of Temnorhynchus coronatus (Fabricius, 1781) is designated. All citations of species of Temnorhynchus are listed with key words. A bibliography of the genus (194 references), a gazetteer of localities and a list of material examined are given. Keywords Coleoptera, Scarabaeoidea, Melolonthidae, Dynastinae, Temnorhynchus Hope, key, catalogue, gazetteer, bibliography. Nomenclatural Acts coronatus (Fabricius, 1781) (Temnorhynchus (Temnorhynchus)), Lectotype described as Scarabaeus coronatus